Organization of tasks distribution by departments of project-oriented university - Онищенко, Светлана Петровна; Логинов, Олег Владимирович (Technology audit and production reserves, 2016)
The tool maintenance is developed for organization of tasks distribution by departments of project-oriented enterprise, which includes: concept, fundamental structure of the information description of tasks in accordance with the project approach, ensuring the distribution of tasks for temporary periods. Methodical approach to identify the tasks of project-oriented university is developed on the basis of the use of "business portfolio" concept, decomposition method and index system by the example of the educational activities of universities. At the same time all the tasks are divided into two categories depending on their nature and the presence of "uniqueness" - standard and specific, allowing to better organize their accounting and can be used to assess the degree of formation of project-oriented university in the proposed measure. The concept of tasks distribution by departments in the system of project-oriented enterprise is formulated. This concept provides the organization of tasks performing with clear structuring objectives, time constraints and the necessary results for each task by a) systematic review of tasks within the network project models, b) integrated consideration of network models corresponding university projects portfolio. Tool maintenance of organization of tasks distribution by departments on the basis of approach to identification of tasks in accordance with the stated concept is developed in terms of set theory.